The Interaction of Aging and Cellular Stress Contributes to Pathogenesis in Mouse and Human Huntington Disease Neurons - Machiela, Emily; Jeloka, Ritika; Caron, Nicholas S.; Mehta, Shagun; Schmidt, Mandi E.; Baddeley, Helen J. E.; Tom, Colton M.; Polturi, Nalini; Xie, Yuanyun; Mattis, Virginia B.; Hayden, Michael R.; Southwell, Amber L. (Frontiers in Aging Neuroscience, 2020)
Huntington disease (HD) is a fatal, inherited neurodegenerative disorder caused by a mutation in huntingtin (HTT). While mutant HTT is present ubiquitously throughout life, HD onset typically occurs in mid-life. Oxidative damage accumulates in the aging brain and is a feature of HD. We sought to interrogate the roles and interaction of age and oxidative stress in HD using primary Hu97/18 mouse neurons, neurons differentiated from HD patient induced pluripotent stem cells (iPSCs), and the brains of HD mice. We find that primary neurons must be matured in culture for canonical stress responses to occur. Furthermore, when aging is accelerated in mature HD neurons, mutant HTT accumulates and sensitivity to oxidative stress is selectively enhanced. Furthermore, we observe HD-specific phenotypes in neurons and mouse brains that have undergone accelerated aging, including selective increase in DNA damage. These findings suggest a role for aging in HD pathogenesis and interaction between biological age of HD neurons and sensitivity to exogenous stress.